Rabindranath Tagore and Hermann Keyserling: A Difficult Friendship - Kämpchen, Germany/India, Martin (Asiatic: IIUM Journal of English Language and Literature, 2011)
Hermann Keyserling, Germany's most influential philosophical writer in the early 20th century, met Rabindranath Tagore in 1911 in Calcutta and noticed his genius before it became known to the world through the Nobel Prize (1913). Keyserling's Travel Diary of a Philosopher (1918) with a long chapter on India continues to be a highly acclaimed work. Keyserling, who was endowed with a tempestuous temperament, tried to monopolise the Indian poet when he visited Germany in 1921. Tagore defended his independence successfully. However, he agreed to conduct the so-called â€œTagore Weekâ€ at Darmstadt where Keyserling lived and had founded his School of Wisdom. While Keyserling always talked of Tagore in a language of superlative praise, it is clear that Rabindranath and his son Rathindranath Tagore were less appreciative of the philosopher and, privately, criticised him because of his domineering manners.